Interactions Among Multiple Quantitative Trait Loci Underlie Rhizome Development of Perennial Rice - Fan, Zhiquan; Wang, Kai; Rao, Jianglei; Cai, Zhongquan; Tao, Li-Zhen; Fan, Yourong; Yang, Jiangyi (Frontiers in Plant Science, 2020)
Perennial crops have some advantages over annuals in soil erosion prevention, lower labor and water requirements, carbon sequestration and maintenance of thriving soil ecosystems. Rhizome, a kind of root-like underground stem, is a critical component of perenniality, which allows many grass species to survive through harsh environment. Identification of rhizome-regulating genes will contribute to the development of perennial crops. There have been no reports on the cloning of such genes until now, which bring urgency for identification of genes controlling rhizomatousness. Using rhizomatous O. longistaminata and rhizome-free cultivated rice as male and female parents, respectively, genetic populations were developed to identify genes regulating rhizome. Both entire population genotyping and selective genotyping mapping methods were adopted to detect rhizome-regulating QTL (quantitative trait loci) in four years. Results showed that multiple genes regulated development of rhizomes, with over ten loci related to rhizome growth. At last, five major-effect loci were identified including qRED1.2, qRED3.1, qRED3.3, qRED4.1 and qRED4.2. It has been found that the individual plant with well-developed rhizomes carried at least three major-effect loci and a certain number of minor-effect loci. Both major-effect and minor-effect loci worked together to control rhizome growth, while no one could work alone. These results will provide new understanding of genetic regulation on rhizome growth and reference to the subsequent gene isolation in rice. And the related research methods and results in this study will contribute to the research on rhizome of other species.